Impaired executive functions in experimental model of temporal lobe epilepsy - Ramos, Fabiane Ochai; Carreiro, Luiz Renato Rodrigues; Scorza, Fulvio Alexandre; Cysneiros, Roberta Monterazzo (Arquivos de Neuro-Psiquiatria, 2016)
Objective The present study aimed to investigate cognitive and behavioural changes consistent with attention deficit hyperactivity disorder (ADHD -like behavior in male Wistar rats with temporal lobe epilepsy (TLE).Method Male Wistar rats at 25 day of age were submitted to animal model of TLE by pilocarpine injection (350 mg/kg, ip) and a control group received saline 0.9%. The animals were continuously video monitored up to the end of experiments. The behavioural tests (open field, elevated plus maze and operant conditioning box) started from 60 days postnatal.Results Animals with TLE exhibited elevated locomotor activity, reduced level of anxiety-related behavior, impulsivity and impaired visuospatial working memory.Conclusion Taken as a whole, we concluded that animals with TLE exhibited some cognitive and behavioural changes consistent with ADHD-like behavior.
Keywords: Epilepsy, temporal lobe; executive function; pilocarpine; memory, short-term